Conceptual Model to Illustrate the Symptom Experience and Humanistic Burden Associated With Atopic Dermatitis in Adults and Adolescents. Issue 4 (July 2019) - Grant, Laura; Seiding Larsen, Lotte; Trennery, Claire; Silverberg, Jonathan I.; Abramovits, William; Simpson, Eric L.; Stalder, Jean-Francois; Paty, Jean; Hahn-Pedersen, Julie; Kragh, Nana; Bang, Bo; Arbuckle, Rob
Abstract : Atopic dermatitis (AD) is a pruritic or painful dermatologic disease characterized by xerosis and eczema lesions. The symptoms/signs of AD can significantly impact patients' health-related quality of life (HRQoL). This study aimed to qualitatively explore the adult and adolescent experience of AD. A targeted literature review and qualitative concept elicitation interviews with clinicians (n = 5), adult AD patients (n = 28), and adolescent AD patients (n = 20) were conducted to elicit AD signs/symptoms and HRQoL impacts experienced. Verbatim transcripts were analyzed using thematic analysis. Twenty-nine symptoms/signs of AD were reported, including pruritus, pain, erythema, and xerosis. Atopic dermatitis symptoms/signs were reported to substantially impact HRQoL. Scratching was reported to influence the experience of symptoms and HRQoL impacts. Four proximal impacts (including discomfort and sleep disturbance) were reported. Ten domains of distal impact were reported, including impacts on psychological and social functioning and activities of daily living. A conceptual model was developed to summarize these findings. This study highlights the range of symptoms and HRQoL impacts experienced by adults and adolescents with AD. To our knowledge, this study was first to explore the lived experience of AD in both adult and adolescent patients, providing valuable insight into the relatively unexplored adolescent experience of AD. Abstract : Supplemental digital content is available in the text.